Mutually reinforcing removal of uranium(VI) and nitrate enabled by pH-buffered nitrogen-doped carbon nanotube-calcium phosphate derived from corn stover and mussel shells - Jun Hu; Weidong Cheng; Yidan Zhang; Jian Ni; Junxia Yin; Wentao Zeng; Yuling Zhu (Bioresource Technology, 2026)

Three-dimensional porous MXene-cellulose aerogel: An efficient adsorbent for sequential capture of Hg(II) and decolorization of methylene blue - Ming Li; Xiaofei Fan; Jianing Hu; Jinghong Zhang; Huining Xiao; Yuling Zhang (Desalination, 2026)

Enhanced nitrogen and phosphorus co-removal mediated by quorum sensing in novel cold-resistant strain LD-01: Mechanisms and application in hyporheic zones during freeze–thaw cycles - Dong Li; Yuling Zhang; Xiaosi Su; Tao Lang; Ruixin Wang; Yuliang Hu (Bioresource Technology, 2026)

Abrupt versus progressive CO2 increases: Overestimation of stimulatory effects on iron-driven anaerobic methane oxidation activity in paddy soils - Wangting Yang; Jinghao Jin; Evgenios Agathokleous; Qinan Hu; Yuling Yang; Bingjie Ren; Yanping Wang; Yuhan Jin; Zhenghua Hu; Lidong Shen (Agriculture, Ecosystems & Environment, 2026)

Wheat properties shape microbial succession and flavor profile in high-temperature Daqu fermentation: a multi-omics perspective - Hongmei Wang; Yuling Shen; Sican Luo; Yongxin Hu; Fuli Wen; Qian Wang; Xi Shen; Hao Shi; Yiping Chen; Xiaozhong Zhong; Songtao Wang; Yang Wei; et al. (Food Research International, 2026)

Electron-bridge-mediated construction of flower-layered Cu@CuO@TCPP-Cu heterojunction from homogeneous copper precursor for integrated SERS and peroxidase-mimicking analysis - Ying Chen; Kun Ge; Xing Liang Cheng; Yuling Hu (Chemical Engineering Journal, 2026)

Cationic Dendrimer-Directed Pore Architecture in Polyamide Membranes for Tunable Ion Separation - Bingbing Yuan; Menghan Wu; Jinmiao Cui; Lei Zhang; Zequn Liao; Ping Hu; Yuling Ren; Lihong Liu; Siheng Zhao; Meng You; Dongxiao Yang; Q. Jason Niu (Water Research, 2026)

Effect of heat-moisture modified sweet potato starch on the microstructure and physicochemical properties of wheat noodles - Wei Wang; Dongdong Huang; Yuling Ma; Yiying Yang; Aijun Hu; Haiyan Gao (Journal of Cereal Science, 2026)

Mussel-inspired engineering of green spherical cellulose adsorbents with PEI/PDA multilayers for efficient and selective mercury capture - Ming Li; Yuxin Gong; Xiaofei Fan; Jianing Hu; Shiwei Guo; Yuling Zhang; Huining Xiao (Desalination, 2026)

Coastal marsh conversion to paddy fields leads to a more pronounced stimulation of temperature sensitivity of soil microbial respiration in higher-latitude regions - Xiaochen Yao; Weiqi Wang; Yuling Yang; Wangting Yang; Bingjie Ren; Qinan Hu; Lidong Shen (Marine Pollution Bulletin, 2026)

Early-rice straw return rnhances Cd accumulation in late-rice through increased soil Cd bioavailability and root uptake in a Cd-contaminated double-cropping rice system - Yuhui Zeng; Geyi Xu; Changsong Huang; Zhong Hu; Qian Qi; Yuling Liu; Xiao Deng; Yang Yang; Changjun Li; Si Luo (Journal of Environmental Sciences, 2026)

Assessing coastal groundwater risks from nuclear-contaminated water discharge under extreme drought and sustainable recharge solutions - Jiao Zhang; Yaqiang Wei; Yuling Chen; Zhenzhong Hu; Damià Barceló; Tian-Chyi Jim Yeh; Jiazhong Qian; Bradley A. Weymer; Zi Zhan; Xinde Cao; Hui Li (Journal of Contaminant Hydrology, 2026)

From importance to sensitivity: fuel consumption analysis of heavy-duty diesel vehicles - Yuling Song; Tianhao Liu; Tiezhu Li; Xiyuan Hu; Ruizhi Zhang; Haibo Chen (Transportation Research Part D: Transport and Environment, 2026)

Ameliorative Effects of an Antioxidant and Anti-Inflammatory Limosilactobacillus fermentum TG017 on DSS-Induced Ulcerative Colitis in Mice - Qianhao Hou; Yuling Li; Zuanyuan Huang; Honghua Hu; Xin Li; Jinyuan Zhang; Wenying Duan; Songsong Pan; Zetian Wang; Xiaodong Liu; Wei Xu; Lijun Liao (Probiotics and Antimicrobial Proteins, 2026)

Antifungal activity and mechanisms of honokiol against Fusarium fujikuroi, the Chinese yew leaf blight pathogen - Yuling Jiang; Yao Charles Meto; Amir Khan; Zhenxiang Guo; Anlong Hu (Physiological and Molecular Plant Pathology, 2026)

Differential clinical factors influencing the effectiveness of distinct biologic agents in psoriasis: insights from a prospective cohort study in China - Min Dai; Yuxiong Jiang; Yuanyuan Wang; Dawei Huang; Yu Wang; Yifan Hu; Yunlu Gao; Qian Yu; Yuling Shi (Inflammation Research, 2026)

Supramolecular calix[6]arene-COF with pocket-like cavities for host-guest recognition-based SERS detection of tryptamine and seafood freshness monitoring - Jiana Lin; Ying Chen; Gongke Li; Yuling Hu (Food Chemistry, 2026)

Stimulation of nitrate-driven AOM potential in paddy soils under elevated atmospheric CO2 concentration - Jinghao Jin; Yuling Yang; Bingjie Ren; Yanping Wang; Yuhan Jin; Wangting Yang; Qinan Hu; Lidong Shen; Zhenghua Hu (Journal of Environmental Management, 2025)

Differences in nighttime radiance across urban residential communities in China - Yi Zhou; Yuling Jin; Gaohui Wen; Xianhui Hu; Hao Zhou; Yuchao Luo; Guohua Zhou; Haile Zhao (Journal of Environmental Management, 2025)

Zeolitic imidazolate frameworks exert bioenergetic modulation via the cAMP/PKA/CREB signaling pathway to accelerate periodontal regeneration - Weiqiang Hu; Xueshen Qian; Xuxin Lin; Qianqian Chen; Zekai Wu; Ziqin Chen; Zhenzhu Xue; Yuling Chen; Xiongcheng Xu; Kai Luo (Chemical Engineering Journal, 2025)

Trophic status impacts the potential significance of anaerobic methane oxidation driven by multiple electron acceptors in Lake Taihu sediments - Wangting Yang; Qinan Hu; Hechen Huang; Jinghao Jin; Bingjie Ren; Sile Wen; Yuling Yang; Yefan He; Yanping Wang; Yanan Bai; Yuzhi Song; Lidong Shen (CATENA, 2025)

Anthropogenic aerosol feedbacks intensify air pollution and weather variability over China - Jixiang Li; Haipeng Yu; Andrea Pozzer; Kai Tang; Chenhui Jia; Zeyong Hu; Siyu Chen; Yunsai Zhu; Yuling Hu; Bofei Zhang; Hongyu Luo; Zekui Jiang; et al. (Atmospheric Environment, 2025)

Genome-wide identification and analysis of paclobutrazol-resistance gene family in cotton and the positive role of GhPRE3 in salt stress and drought stress resistance - Shuaikang Geng; Jingjing Zhai; Bingkai Cui; Huiyun Shan; Zili Liu; Jiahui Li; Cong Wang; Yuling Liu; Pengtao Li; Quanwei Lu; Zihan Xiao; Xiaoping Pan; et al. (Functional & Integrative Genomics, 2025)
Compared with other transcription factors, much less studies have been performed on paclobutrazol-resistance (PRE), a subgroup of the extensive bHLH transcription factor gene family, and the research in cotton was also limited. By utilizing the PRE genes and their conserved domains identified in Arabidopsis, a total of 23, 22, 11, and 12 PRE genes were identified from two major cultivated cotton species and their two ancestors, respectively. The cotton PRE gene family was categorized into three subgroups based on evolutionary tree analysis. Motif and intron analyses indicated that the PRE gene has remained highly conserved throughout evolution. Collinearity analysis indicated that gene duplication, particularly through fragment replication, has significantly contributed to the expansion of the cotton PRE family. An exploration of the conserved elements within the PRE gene family uncovered numerous elements associated with plant stress resistance. Additionally, cotton transcriptome and qRT-PCR analysis showed that PRE genes were associated with a variety of abiotic stresses, including salt, drought, and cold treatments. Subcellular localization experiments indicated that the GhPRE3 gene is associated with membrane proteins. Finally, we selected the GhPRE3 gene for a VIGS experiment, which revealed that under salt stress and drought stress conditions, the wilting of leaves in the GhPRE3- silenced plants was significantly more severe than that observed in the control group, with T-AOC levels notably lower and MDA levels significantly higher. Overexpression of GhPRE3 enhanced seed germination and root development in transgenic Arabidopsis thaliana under salt stress and drought stresses. This suggests that GhPRE3 plays a positive regulatory role in cotton tolerance to salt and drought stressed, providing a reference for molecular genetic breeding of cotton with salt and drought tolerance.

Identification of the STY13 gene family across the entire genome and an analysis of the essential function of GhSTY13-12 in cotton’s response to abiotic stress - Shaoliang Zhang; Huiyun Shan; Xiaopei Bo; Jiahui Li; Zili Liu; Pengtao Li; Yuling Liu; Xiaojie Yang; Quanwei Lu; Sumei Wan; Renhai Peng; Yangyang Wei; et al. (Functional & Integrative Genomics, 2025)

Fluorine-decorated rare-earth hydroxides mediated preparation of hollow low-iridium oxyfluoride for highly efficient oxygen evolution reaction catalyst - Yuling Hu; Zhen Zeng; Yun Liu; Hao Zhang; Wenjuan Shi; Zhengye Kang; Yuliang Yuan; Wei Sun; Xinlong Tian (Chemical Engineering Journal, 2025)

Microplastics and gynecological tumors: An emerging environmental health concern - Yuling HU; Zhihui SONG; Jingwen LI; Feiyi YANG; Ling LI (Reproductive Toxicology, 2025)

Untargeted lipidomic deep-profiling of human plasma via high-performance aza-Prilezhaev aziridination-LC-MS: Unraveling C C isomeric signatures of Charcot-Marie-Tooth disease - Yuling Li; Weiran Zhao; Xiang Xiang; Yunlei Hu; Xiaoqiang Zhang; Wenjian Sun; Xiaoxuan Liu (Analytica Chimica Acta, 2025)

First report of Fusarium fujikuroi causing leaf blight on Chinese yew - Yao Charles Meto; Guoyu Wei; Huayang Xu; Yuling Jiang; Hongfei Gao; Anlong Hu (Crop Protection, 2025)

Novel EDTA modified steel slag-based catalyst for NO removal through heterogeneous Fenton processes - Lingtao Liu; Yuan Xu; Zihua Hu; Jianying Yang; Zhuyao Li; Yuling Zhu; Jianhua Ding; Jiawei Li; Feiqiang He (Journal of Hazardous Materials, 2025)

Efficient large-scale vegetation mapping at the formation level using multi-source data: A case study in Beijing, China - Jiachen Xu; Yongmei Huang; Kai Cheng; Yi Wang; Tianyu Hu; Hongcan Guan; Yuling Chen; Yu Ren; Mengxi Chen; Zekun Yang; Jiarui Wang; Qinghua Guo (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Afforestation increases glomalin-related soil protein content and enhances its association with stable soil carbon in karst regions - Lei Xie; Qiumei Ling; Peilei Hu; Yuling Zhang; Wei Zhang; Yuan Zhao; Kelin Wang (Forest Ecology and Management, 2025)

Impact of conversion of coastal wetlands into paddy fields on the process of nitrite-dependent anaerobic methane oxidation - Qinan Hu; Weiqi Wang; Wangting Yang; Yuling Yang; Yanan Bai; Yefan He; Bingjie Ren; Yanping Wang; Jinghao Jin; Lidong Shen (Soil Ecology Letters, 2025)

Effective SSR markers for assessing population structure, genetic diversity, and volatile compounds in Atractylodis Rhizoma - Haotian Zhong; Lina Chen; Lei Chen; Xiao Huang; Ling Gong; Juan Hu; Yuling Zeng; Kun Yu; Lin Sen (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

Correction to: Failure mechanism and stability evaluation of rockslides with oblique intersecting faults as well as mitigation measures for slope − top platform collapse - Huaixin Li; Changgen Yan; Yuling Shi; Hengxing Lan; Han Bao; Weifeng Sun; Zhe He; Dingle Ma; Kui Wen; Jiamin Hu (Landslides, 2025)

How many trees are there in China? - Kai Cheng; Haitao Yang; Yuling Chen; Zekun Yang; Yu Ren; Yixuan Zhang; Danyang Lin; Weiyan Liu; Guoran Huang; Jiachen Xu; Mengxi Chen; Zhiyong Qi; et al. (Science Bulletin, 2025)

Comparative transcriptomic analysis of heterotic maize development during kernel filling - Wenyu Li; Xiangkun Guo; Wen Yao; Keke Li; Qi Zheng; Yongbiao Yu; Zhiwei Zhang; Yan Wang; Weigang Yao; Ju Wu; Huan Hu; Lingwei Hu; et al. (Plant Molecular Biology, 2025)

Failure mechanism and stability evaluation of rockslides with oblique intersecting faults as well as mitigation measures for slope − top platform collapse - Huaixin Li; Changgen Yan; Yuling Shi; Hengxing Lan; Han Bao; Weifeng Sun; Zhe He; Dingle Ma; Kui Wen; Jiamin Hu (Landslides, 2025)

Conversion of coastal wetlands to paddy fields substantially decreases methane oxidation potential and methanotrophic abundance on the eastern coast of China - Yuling Yang; Weiqi Wang; Qinan Hu; Xiaochen Yao; Wangting Yang; Sile Wen; Haikun Wu; Jinghao Jin; Lidong Shen (Water Research, 2025)

Encapsulation of oleanolic acid into cyclodextrin metal-organic frameworks by co-crystallization: Preparation, structure characterization and its effect on a zebrafish larva NAFLD model - Meng Li; Dongxia Hu; Dian Zhang; Guangya Xu; Di Wu; Chengcheng Gao; Linghan Meng; Xiao Feng; Weiwei Cheng; Zhenjiong Wang; Yuling Yang; Xiaozhi Tang (Food Research International, 2025)

A new insight into the straw decomposition associated with minerals: Promoting straw humification and Cd immobilization - Yuling Liu; Haowei Zeng; Siduo Ding; Zhong Hu; Baiqing Tie; Si Luo (Journal of Environmental Sciences, 2025)

Host-guest mediated recognition and rapid extraction of Fusarium mycotoxins in cereals by nickel ferrite magnetic calix[4]arene-derived covalent organic framework fabricated in room-temperature - Jiana Lin; Gongke Li; Yuling Hu; Qisheng Zhong (Food Chemistry, 2025)

Biochar supporting and sulfidation synergistically affect reactivity of nanoscale zerovalent iron towards sulfamethoxazole - Mi Li; Tiao Zhang; Jing Wang; Xiaoyu Xiao; Xinyi Zeng; Cui Hu; Xiaoming Zou; Wei Hui; Yuling Zheng (Chemical Engineering Journal, 2025)

LINC01224 promotes the Warburg effect in gastric cancer by activating the miR-486-5p/PI3K axis - Yuling Bin; Minji Liu; Rong He; Pingfei Tang; Weiming Qu; Dajun Wu; Lin Tan; Qian Wang; Peng Jiang; Hongsai Hu (In Vitro Cellular & Developmental Biology - Animal, 2025)

Hyperbranched polymer wrapped UIO-66-NH2 as covalent intermediate layer to enhance polyamide membrane for Li+/Mg2+ separation and acid/alkaline stability - Bingbing Yuan; Shuang Yuan; Chaozheng Jia; Ping Hu; Siheng Zhao; Yuling Ren; Meng You; Shengchao Zhao; Kuo Chen; Xiaozhuan Zhang; Dongxiao Yang; Juhui Jiang; et al. (Desalination, 2025)

Responses of suspended sludge and biofilm in a SNAD system under C/N elevation: Microbial activity, nitrogen conversion flux and molecular ecological network - Junyu Liu; Meina Hu; Mei Hu; Jiaao Wang; Tingting Zhang; Yuling Wang; Xiaohui Wang (Science of The Total Environment, 2024)

Defect-controlled confined growth of nano-MOFs to prepare materials with hierarchical micro/mesoporous structures for efficient CO2 capture - Xuewen Chen; Hongping Quan; Zhengyan Zhou; Xiaofeng Zhang; Yuling Hu; Zhiyu Huang (Journal of Environmental Chemical Engineering, 2024)

Spatio-temporal variations in activity of aerobic methane oxidation and community structure of methanotrophs in sediment of Wuxijiang river - Yefan He; Yuling Yang; Hechen Huang; Wangting Yang; Bingjie Ren; Qinan Hu; Jinghao Jin; Sile Wen; Haixiang Cheng; Lidong Shen (Environmental Pollution, 2024)

Determining optimal nitrogen concentration intervals throughout lettuce growth using fluorescence parameters - Peizhe Li; Zhangtong Sun; Yongxia Yang; Miao Lu; Huimin Li; Haoran Yan; Jin Hu; Yuling Song (Computers and Electronics in Agriculture, 2024)

Effects of wheat germ treated with different stabilization methods on dough characteristics and steamed bread quality - Gongqi Zhao; Shiqiang Hu; Qianqian Huang; Yuling Yang; Ligong Zhai; Qian Gao; Liping Yang (Journal of Cereal Science, 2024)

Stimulation of methane production potential and alteration in community composition of methanogens following conversion of China’s coastal marshes to paddy fields - Xiaochen Yao; Weiqi Wang; Yuling Yang; Wangting Yang; Qinan Hu; Jinghao Jin; Jiaqi Liu; Yuchao Wang; Lidong Shen (CATENA, 2024)

N, S, Se-Codoped dual carbon encapsulation and Se substitution in pyrite-type FeS2 for high-rate and long-life sodium-ion batteries - Yuling Shi; Peng Mei; Tingting He; Chengjiang Deng; Haocun Ba; Junping Hu; Shaozhuan Huang (Chemical Engineering Journal, 2024)

Aging properties of polyethylene and polylactic acid microplastics and their adsorption behavior of Cd(II) and Cr(VI) in aquatic environments - Xinying Zhang; Yuling Zhang; Dong Li; Jili Wang; Yang Ding; Yiliang Wang; Liuyuan Feng; Yuliang Hu (Chemosphere, 2024)

Rapid construction of double macrocycles, hierarchical covalent organic framework with size-sieving and host-guest recognition for selective adsorption and targeted analysis of mycotoxins in cereals - Zenghui Xie; Jiana Lin; Yuling Hu; Gongke Li; Qisheng Zhong (Chemical Engineering Journal, 2024)

Effects of soil aggregates and minerals on microbial necromass carbon are regulated by parent materials - Lei Xie; Peilei Hu; Qiumei Ling; Wei Zhang; Pengpeng Duan; Yuling Zhang; Kelin Wang (Applied Soil Ecology, 2024)

Bi-directional association between outdoor or social activities and cognitive function: do the PM2.5 exposure catalyze the detrimental inactivity-poor cognition cycle? - Yuling Jiang; Yifei Wu; Yang Hu; Shaojie Li; Longbin Ren; Jingjing Wang; Mingzhi Yu; Rui Yang; Zhouwei Liu; Nan Zhang; Kejia Hu; Yunquan Zhang; et al. (Environmental Research, 2024)

Plant regeneration in the new era: from molecular mechanisms to biotechnology applications - Chunli Chen; Yuxin Hu; Momoko Ikeuchi; Yuling Jiao; Kalika Prasad; Ying Hua Su; Jun Xiao; Lin Xu; Weibing Yang; Zhong Zhao; Wenkun Zhou; Yun Zhou; et al. (Science China Life Sciences, 2024)

South and Southeast Asia controls black carbon characteristics of Meili Snow Mountains in southeast Tibetan Plateau - Pengfei Chen; Shichang Kang; Yuling Hu; Tao Pu; Yajun Liu; Shijin Wang; Mukesh Rai; Ke Wang; Lekhendra Tripathee; Chaoliu Li (Science of The Total Environment, 2024)

Modeling the transport of PM10, PM2.5, and O3 from South Asia to the Tibetan Plateau - Yuling Hu; Haipeng Yu; Shichang Kang; Junhua Yang; Xintong Chen; Xiufeng Yin; Pengfei Chen (Atmospheric Research, 2024)

Enhanced cadmium absorption and tolerance of rice epiphytic microbes by iron oxide nanoparticles - Siduo Ding; Zhong Hu; Yuling Liu; Li Li; Yuhui Zeng; Doudou Jin; Anwei Chen; Jihai Shao; Pin Su; Si Luo (International Biodeterioration & Biodegradation, 2024)

Weakened black carbon trans-boundary transport to the Tibetan Plateau during the COVID-19 pandemic - Ye Zhou; Junhua Yang; Shichang Kang; Yuling Hu; Xintong Chen; Mian Xu; Mengmeng Ma (Science of The Total Environment, 2024)

"Needle" hidden in silk floss: Inactivation effect and mechanism of melamine sponge loaded bismuth oxide composite copper-metal organic framework (MS/Bi2O3@Cu-MOF) as floating photocatalyst on Microcystis aeruginosa - Mengjiao Wang; Junfeng Chen; Yushan Wei; Lijun Hu; Yuling Xu; Yanyan Liu; Renjun Wang (Journal of Hazardous Materials, 2024)

Development of composite amine functionalized polyester microspheres for efficient CO2 capture - Xuewen Chen; Hongping Quan; Jie Yu; Yuling Hu; Zhiyu Huang (Environmental Science and Pollution Research, 2023)

Research status and prospects of organic photocatalysts in algal inhibition and sterilization: a review - Yushan Wei; Renjun Wang; Mengjiao Wang; Lijun Hu; Xinyi Zhang; Yuling Xu; Yanyan Liu; Feng Lan; Junfeng Chen (Environmental Science and Pollution Research, 2023)

The selection of floating photocatalyst carrier and algae inhibition effect of Karenia mikimotoi based on SNP-TiO2@Cu-MOF under visible light - Renjun Wang; Lijun Hu; Mengjiao Wang; Yushan Wei; Yuling Xu; Xinyi Zhang; Junfeng Chen (Chemosphere, 2023)

Research progress and prospect of metal-organic framework and covalent-organic framework for photocatalytic treatment of harmful algal blooms - Mengjiao Wang; Junfeng Chen; Yushan Wei; Lijun Hu; Yuling Xu; Yanyan Liu; Renjun Wang (Journal of Water Process Engineering, 2023)

Contributions of biomass burning in 2019 and 2020 to Arctic black carbon and its transport pathways - Xintong Chen; Shichang Kang; Junhua Yang; Yuling Hu (Atmospheric Research, 2023)

Springtime biomass burning impacts air quality and climate over the Tibetan Plateau - Junhua Yang; Shichang Kang; Yuling Hu; Xintong Chen; Mukesh Rai (Atmospheric Environment, 2023)

Calix[4]arene-based covalent organic frameworks with host-guest recognition for selective adsorption of six per- and polyfluoroalkyl substances in food followed by UHPLC-MS/MS detection - Zenghui Xie; Yuling Hu; Jiana Lin; Gongke Li; Qisheng Zhong (Journal of Hazardous Materials, 2023)

Dkk-1–TNF-α crosstalk regulates MC3T3E1 pre-osteoblast proliferation and differentiation under mechanical stress through the ERK signaling pathway - Yeke Wu; Zheng Jing; Disi Deng; Jin Yan; Min Liu; Li Li; Yuling Zuo; Wenbin Wu; Qiongying Hu; Yunfei Xie (Molecular and Cellular Biochemistry, 2023)

Effect of agricultural carbon emissions on farmers’ health expenditure of China: evidence from the educational threshold effect - Yuling Hu; Junyin Tan; Na Zhang; Chengjie Liu (Environmental Science and Pollution Research, 2023)

Manipulating polysulfide catalytic conversion through edge site construction, hybrid phase engineering, and Se anion substitution for kinetics-enhanced lithium-sulfur battery - Tong Li; Zhouhao Wang; Junping Hu; Haobin Song; Yuling Shi; Yu Jiang; Daohong Zhang; Shaozhuan Huang (Chemical Engineering Journal, 2023)

Responses of soil carbon cycling microbial functional genes to nitrogen and phosphorus addition in saline-sodic soils - Xuejun Du; Yanning Ge; Yun Zhang; Hao Hu; Yiying Zhang; Ziye Yang; Xueqin Ren; Shuwen Hu; Haojie Feng; Yuling Song (Plant and Soil, 2023)

Comparative Analysis of the Therapeutic Effects of Fresh and Cryopreserved Human Umbilical Cord Derived Mesenchymal Stem Cells in the Treatment of Psoriasis - Zhifeng Wang; Yifan Hu; Xiaoyu Wang; Youdong Chen; Danfeng Wu; Houli Ji; Cuicui Yu; Jingmeng Fang; Chunrong Pan; Lianjian Wang; Shouxin Wang; Yinhong Guo; et al. (Stem Cell Reviews and Reports, 2023)

Neutralizing Antibody Validation Testing and Reporting Harmonization - Heather Myler; João Pedras-Vasconcelos; Todd Lester; Francesca Civoli; Weifeng Xu; Bonnie Wu; Inna Vainshtein; Linlin Luo; Mohamed Hassanein; Susana Liu; Swarna Suba Ramaswamy; Johanna Mora; et al. (The AAPS Journal, 2023)
Evolving immunogenicity assay performance expectations and a lack of harmonized neutralizing antibody validation testing and reporting tools have resulted in significant time spent by health authorities and sponsors on resolving filing queries. A team of experts within the American Association of Pharmaceutical Scientists’ Therapeutic Product Immunogenicity Community across industry and the Food and Drug Administration addressed challenges unique to cell-based and non-cell-based neutralizing antibody assays. Harmonization of validation expectations and data reporting will facilitate filings to health authorities and are described in this manuscript. This team provides validation testing and reporting strategies and tools for the following assessments: (1) format selection; (2) cut point; (3) assay acceptance criteria; (4) control precision; (5) sensitivity including positive control selection and performance tracking; (6) negative control selection; (7) selectivity/specificity including matrix interference, hemolysis, lipemia, bilirubin, concomitant medications, and structurally similar analytes; (8) drug tolerance; (9) target tolerance; (10) sample stability; and (11) assay robustness. Graphical Abstract

Corrigendum to “Accumulation of dissolved organic matter in the transition from fresh to aged seasonal snow in an industrial city in NE China” [Sci. Total Environ. 857 (2023) 159337] - Zhen Mu; Xiaoying Niu; Christian George; Xinke Wang; Rujin Huang; Yuling Ma; Wei Pu; Yulin Qi; Pingqing Fu; Junjun Deng; Chao Ma; Nan Hu; et al. (Science of The Total Environment, 2023)

Effects of different semen extenders on sperm motility and pregnancy rates in donkeys - Xuan Wu; Yuling Hu; Yajun Guo; Shenming Zeng (Journal of Equine Veterinary Science, 2023)

The effect of vacancy defective Mg (0001) surface on hydrogenation of Ni-Mg-CNTs: A mechanistic investigation - Congwen Duan; Mengmeng Wu; Xinya Wang; Dong Fu; Yuling Zhang; Wei Lv; Lianxi Hu; Ming Li; Fei Wang; Ying Wu (Fuel, 2023)

Ameliorative effect of calcium poly(aspartic acid) (PASP-Ca) and calcium poly-γ-glutamic acid (γ-PGA-Ca) on soil acidity in different horizons - Fei Kang; Qilin Lv; Jingbiao Fan; Yun Zhang; Yuling Song; Xueqin Ren; Shuwen Hu (Environmental Science and Pollution Research, 2023)

Spatio-temporal variations of activity of nitrate-driven anaerobic oxidation of methane and community structure of Candidatus Methanoperedens-like archaea in sediment of Wuxijiang river - Haixiang Cheng; Yuling Yang; Yefan He; Xugang Zhan; Yan Liu; Zhengfeng Hu; Hechen Huang; Xiaochen Yao; Wangting Yang; Jinghao Jin; Bingjie Ren; Jiaqi Liu; et al. (Chemosphere, 2023)

Migration detection of six aromatic amines in polyamide food contact materials by HPLC after molecularly imprinted polymer pipette tip solid phase extraction - Yang Liu; Xueping Dang; Shicheng Zhang; Yuling Hu; Huaixia Chen (Food Packaging and Shelf Life, 2023)

Effects of abrupt and gradual increase of atmospheric CO2 concentration on methanotrophs in paddy fields - Lidong Shen; Bingjie Ren; Yuhan Jin; Xin Liu; Jinghao Jin; Hechen Huang; Maohui Tian; Wangting Yang; Yuling Yang; Jiaqi Liu; Caiyu Geng; Yanan Bai; et al. (Environmental Research, 2023)

Large-scale metabolome analysis reveals dynamic changes of metabolites during foxtail millet grain filling - Tao Wang; Lu Xing; Hui Song; Yangyang Wei; Pengtao Li; Quanwei Lu; Nan Hu; Yuling Liu; Yongqing Zhao; Jinrong Liu; Baohong Zhang; Renhai Peng (Food Research International, 2023)

Immobilizing arsenic in soil via amine metal complex: a case study using iron-ethylenediamine - Qilin Lv; Tairan Zhou; Tianhao Wang; Shuhan Wang; Yanning Ge; Yuling Song; Xueqin Ren; Shuwen Hu (Environmental Science and Pollution Research, 2023)

Estimating the prevalence of hypertension in 164 cities in China by wastewater-based epidemiology - Chenzhi Hou; Yuling Zhong; Lan Zhang; Muyuan Liu; Fang Yan; Mengyi Chen; Youmei Wang; Peng Xu; Mengxiang Su; Chi Hu; Bin Di (Journal of Hazardous Materials, 2023)

Biomass-derived polyphosphazene toward simultaneously enhancing the flame retardancy and mechanical properties of epoxy resins - Yuling Xiao; Xiaowei Mu; Siqi Chen; Guangyong Jiang; Zhoumei Xu; Chao Ma; Lei Song; Yuan Hu (Chemosphere, 2023)

Accumulation of dissolved organic matter in the transition from fresh to aged seasonal snow in an industrial city in NE China - Zhen Mu; Xiaoying Niu; Christian George; Xinke Wang; Rujin Huang; Yuling Ma; Wei Pu; Yulin Qi; Pingqing Fu; Junjun Deng; Chao Ma; Nan Hu; et al. (Science of The Total Environment, 2023)

Photocatalytic degradation effect and mechanism of Karenia mikimotoi by non-noble metal modified TiO2 loading onto copper metal organic framework (SNP-TiO2@Cu-MOF) under visible light - Lijun Hu; Junfeng Chen; Yushan Wei; Mengjiao Wang; Yuling Xu; Chao Wang; Peike Gao; Yanyan Liu; Chunchen Liu; Yuhao Song; Ning Ding; Xiaomei Liu; et al. (Journal of Hazardous Materials, 2023)

Effective enrichment and detection of bisphenol diglycidyl ether, novolac glycerol ether and their derivatives in canned food using a novel magnetic sulfonatocalix[6]arene covalent cross-linked polymer as the adsorbent - Zenghui Xie; Yuling Hu; Yanlong Chen; Gang Wu; Gongke Li; Qisheng Zhong (Food Chemistry, 2023)

Heterogeneous interfacial photocatalysis for the inactivation of Karenia mikimotoi by Bi2O3 loaded onto a copper metal organic framework (Bi2O3@Cu-MOF) under visible light - Mengjiao Wang; Junfeng Chen; Lijun Hu; Yushan Wei; Yuling Xu; Chao Wang; Peike Gao; Yanyan Liu; Chunchen Liu; Yuhao Song; Ning Ding; Xiaomei Liu; et al. (Chemical Engineering Journal, 2023)

The reaction mechanism of highly dispersed Cu atoms and ultrafine MnOx nanoclusters co-modified ZSM-5 based on in-situ heteronuclear substitution for catalytic oxidation C6H14 - Jian Li; Jingnan Hu; Yingjie Shi; Jiajia Zhao; Hongchang Wang; Shuang Deng; Yutao Cui; Fan Wang; Hongyan Long; Yuling Tan (Chemical Engineering Journal, 2023)

A novel phosphorus-, nitrogen- and sulfur-containing macromolecule flame retardant for constructing high-performance epoxy resin composites - Guangyong Jiang; Yuling Xiao; Ziyan Qian; Yuting Yang; Pengfei Jia; Lei Song; Yuan Hu; Chao Ma; Zhou Gui (Chemical Engineering Journal, 2023)

Research progress of photocatalysis for algae killing and inhibition: a review - Lijun Hu; Renjun Wang; Mengjiao Wang; Yuling Xu; Chao Wang; Yanyan Liu; Junfeng Chen (Environmental Science and Pollution Research, 2022)

Influence of South Asian Biomass Burning on Ozone and Aerosol Concentrations Over the Tibetan Plateau - Junhua Yang; Shichang Kang; Yuling Hu; Xintong Chen; Mukesh Rai (Advances in Atmospheric Sciences, 2022)

Human umbilical cord-derived mesenchymal stem cells ameliorate psoriasis-like dermatitis by suppressing IL-17-producing γδ T cells - Youdong Chen; Yifan Hu; Xue Zhou; Zihan Zhao; Qian Yu; Zeyu Chen; Yuanyuan Wang; Peng Xu; Zengyang Yu; Chunyuan Guo; Xilin Zhang; Yuling Shi (Cell and Tissue Research, 2022)

Effects of roasting and deodorisation on 3-monochloropropane-1, 2-diol esters, 3, 4-benzopyrene and trans fatty acids in peanut oil - Pan Gao; Yuling Zheng; Hui Liu; Wei Yang; Chuanrong Hu; Dongping He (Food Additives & Contaminants: Part A, 2022)

Plant multiscale networks: charting plant connectivity by multi-level analysis and imaging techniques - Xi Zhang; Yi Man; Xiaohong Zhuang; Jinbo Shen; Yi Zhang; Yaning Cui; Meng Yu; Jingjing Xing; Guangchao Wang; Na Lian; Zijian Hu; Lingyu Ma; et al. (Science China Life Sciences, 2021)

Protective effects of SP600125 on mice infected with H1N1 influenza A virus - Yuling Tang; Guanghui Yang; Yuxiang Li; Ming Wang; Gebin Li; Yanxin Hu (Archives of Virology, 2021)

Correction to: The Preliminary Study on the Association Between PAHs and Air Pollutants and Microbiota Diversity - Jinye Hu; Yuling Bao; Yuqi Zhu; Ranagul Osman; Mengfan Shen; Zhan Zhang; Li Wang; Shuyuan Cao; Lei Li; Qian Wu (Archives of Environmental Contamination and Toxicology, 2021)

The Preliminary Study on the Association Between PAHs and Air Pollutants and Microbiota Diversity - Jinye Hu; Yuling Bao; Yuqi Zhu; Ranagul Osman; Mengfan Shen; Zhan Zhang; Li Wang; Shuyuan Cao; Lei Li; Qian Wu (Archives of Environmental Contamination and Toxicology, 2020)

Transposon-based screen identifies a XRE family regulator crucial for candicidin biosynthesis in Streptomyces albus J1074 - Jun Tian; Leixin Ye; Yuling Yang; Yalin Zhang; Changhua Hu; Guojian Liao (Science China Life Sciences, 2020)

A quantitative assessment of the air pollution purification effect of a super strong cold-air outbreak in January 2016 in China - Yuling Hu; Shigong Wang; Guicai Ning; Ying Zhang; Jiaxin Wang; Ziwei Shang (Air Quality, Atmosphere & Health, 2018)

Verification and fine mapping of qGW1.05, a major QTL for grain weight in maize (Zea mays L.) - Qiang Zhou; Yongbin Dong; Qingling Shi; Long Zhang; Huanqing Chen; Chunhui Hu; Yuling Li (Molecular Genetics and Genomics, 2017)

Ectopic expression of the maize ZmADF3 gene in Arabidopsis revealing its functions in kernel development - Dahe Qiao; Yongbin Dong; Long Zhang; Qiang Zhou; Chunhui Hu; Yangliu Ren; Yuling Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Extreme monthly precipitation pattern in China and its dependence on Southern Oscillation - Shiquan Wan; Yuling Hu; Zhiyuan You; Jianpeng Kang; Jianguo Zhu (International Journal of Climatology, 2013)
Using the generalized Pareto distribution (GPD) and a spatial scheme of parameter estimation, spatial patterns of extreme monthly precipitation (EMP) in China were studied using 740 stations' data from 1960 to 2007. The spatial patterns of EMP are described by the GPD's scale and shape parameters, whose regional features depend on ENSO activities. The results show that the scale parameter (representing variability) in monsoon areas, such as southern China, is greater than that of non‐monsoon areas, such as northern China, and that it is greater in summer than that in autumn. The shape parameter (representing record‐breaking probability) reaches a maximum in non‐monsoon areas and a minimum in monsoon areas. For the time scale, record‐breaking events would occur more easily in the seasons other than summer. The regional difference in terms of dependence of EMP's variability on Southern Oscillation (SO) was also related to the monsoon transition zone. The variability with great dependence on SO was in the Qinghai–Tibet Plateau and in the region between the Yangtze and Yellow rivers, which are dry–wet transition zones. The response of EMP's record‐breaking probability to SO is apparent in most regions of China, and its spatial pattern becomes the largest in summer and much smaller in spring and autumn. Copyright © 2012 Royal Meteorological Society

Induction of apoptosis in HepG2 cells by polysaccharide MEP-II from the fermentation broth of Morchella esculenta - Meili Hu; Yan Chen; Cui Wang; Huali Cui; Peilu Duan; Tianlong Zhai; Yuling Yang; Shaofei Li (Biotechnology Letters, 2013)

Effects of vegetation control on ecosystem water use efficiency within and among four grassland ecosystems in China - ZHONGMIN HU; GUIRUI YU; YULING FU; XIAOMIN SUN; YINGNIAN LI; PEILI SHI; YANFEN WANG; ZEMEI ZHENG (Global Change Biology, 2008)
Through 2–3‐year (2003–2005) continuous eddy covariance measurements of carbon dioxide and water vapor fluxes, we examined the seasonal, inter‐annual, and inter‐ecosystem variations in the ecosystem‐level water use efficiency (WUE, defined as the ratio of gross primary production, GPP, to evapotranspiration, ET) at four Chinese grassland ecosystems in the Qinghai‐Tibet Plateau and North China. Representing the most prevalent grassland types in China, the four ecosystems are an alpine swamp meadow ecosystem, an alpine shrub‐meadow ecosystem, an alpine meadow‐steppe ecosystem, and a temperate steppe ecosystem, which illustrate a water availability gradient and thus provide us an opportunity to quantify environmental and biological controls on ecosystem WUE at different spatiotemporal scales. Seasonally, WUE tracked closely with GPP at the four ecosystems, being low at the beginning and the end of the growing seasons and high during the active periods of plant growth. Such consistent correspondence between WUE and GPP suggested that photosynthetic processes were the dominant regulator of the seasonal variations in WUE. Further investigation indicated that the regulations were mainly due to the effect of leaf area index (LAI) on carbon assimilation and on the ratio of transpiration to ET ( T /ET). Besides, except for the swamp meadow, LAI also controlled the year‐to‐year and site‐to‐site variations in WUE in the same way, resulting in the years or sites with high productivity being accompanied by high WUE. The general good correlation between LAI and ecosystem WUE indicates that it may be possible to predict grassland ecosystem WUE simply with LAI. Our results also imply that climate change‐induced shifts in vegetation structure, and consequently LAI may have a significant impact on the relationship between ecosystem carbon and water cycles in grasslands.

A mixture model approach to the mapping of QTL controlling endosperm traits with bulked samples - Xuefeng Wang; Zhiqiu Hu; Wei Wang; Yuling Li; Yuan-Ming Zhang; Chenwu Xu (Genetica, 2007)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)